Violenza di genere. Strumenti giuridici e di contrasto - Angeli, Valentina (Il sogno della farfalla, 2020)
The aim of this article is to discuss gender violence legislation by analysing the existing jurisdictional application with an international perspective. By reviewing the conclusions and objectives proposed at the United Nations conferences, the author particularly focuses on the analysis of the causes determining gender violence. This paper highlights a cultural absence in identifying the underlying causes. These are exclusively considered as expression of social and gender power relationships determined by a patriarchal culture. However, the author draws the attention on the lack of a psychodynamic interpretation of this phenomenon. The article concludes by hoping for a future change of perspective in this direction which could represent a valuable cultural enrichment and therefore a potential social and effective antidote against gender violence.